2020
DOI: 10.21203/rs.3.rs-29599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Thylakoid-Rich Spinach Extract Combined with the Calorie-Restricted Diet on Cardiometabolic Risk Factors in Obese Women with Polycystic Ovary Syndrome: A Randomized Controlled Clinical Trial

Abstract: Background: The polycystic ovary syndrome (PCOS) was associated with a higher risk of cardiovascular diseases, related to metabolic dysfunction, due to its peculiar hormonal pattern, dyslipidemia, and inflammatory state. This study was aimed to investigate the effects of thylakoid-rich spinach extract supplementation combined with a hypocaloric diet on cardiometabolic risk factors in obese women with PCOS. Methods: In a double-blind, placebo-controlled design, forty-eight participants (age 20–45 years) consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…By the same token, findings in an animal model of polycystic ovary syndrome (PCOS) indicated that thylakoid-treated rats showed reduced weight, attenuated HOMA-IR and insulin levels, and improved serum concentrations of lipids ( 58 ). There is, however, little information on spinach-derived thylakoid combined with exercise training on adipose tissue derived mediators, but other reports suggest that consumption of 5 g/day thylakoid-rich spinach extract along with calorie-restrictive diet in obese women improved abdominal obesity parameters, insulin resistance, and lipid profiles while decreasing the levels of inflammatory cytokines such as hs-CRP compared to the calorie-restrictive diet alone ( 59 ). However, some studies reported that spinach-derived thylakoid combined with calorie-restriction affect adipokine levels and caused significant downregulation of chemerin and upregulation of omentin in the obese women, likely due to decreases in body weight, fat mass, and BMI ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same token, findings in an animal model of polycystic ovary syndrome (PCOS) indicated that thylakoid-treated rats showed reduced weight, attenuated HOMA-IR and insulin levels, and improved serum concentrations of lipids ( 58 ). There is, however, little information on spinach-derived thylakoid combined with exercise training on adipose tissue derived mediators, but other reports suggest that consumption of 5 g/day thylakoid-rich spinach extract along with calorie-restrictive diet in obese women improved abdominal obesity parameters, insulin resistance, and lipid profiles while decreasing the levels of inflammatory cytokines such as hs-CRP compared to the calorie-restrictive diet alone ( 59 ). However, some studies reported that spinach-derived thylakoid combined with calorie-restriction affect adipokine levels and caused significant downregulation of chemerin and upregulation of omentin in the obese women, likely due to decreases in body weight, fat mass, and BMI ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of our study is that spinach-derived thylakoid supplementation alone or in combination with HIFT modulates adipokine levels in obese men, and that consuming spinach-derived thylakoid amplified the anti-inflammatory effects of HIFT function. Thylakoids can lead to positive outcomes in overweight and obesity and their related disorders by inducing satiety and suppression of hunger sensations, lowering body fat and weight, enhancing glucose homeostasis, reducing serum lipids, attenuating oxidative stress and inflammation, and reducing the absorption of dietary fat and carbohydrate (56). Thylakoids has anti-obesity activities, stimulating insulin sensitivity and improving the lipid profile through delayed glucose and lipid absorption respectively (57).…”
Section: Discussionmentioning
confidence: 99%